Pengaruh PDB, inflasi, tingkat suku bunga, dan nilai tukar Rupiah terhadap indeks harga saham JAKPROP yang terdaftar di Bursa Efek Indonesia - Gunawan, Chendra; Firdausy, Carunia Mulya (Jurnal Manajemen Bisnis dan Kewirausahaan, 2017)
This research aims to find out and analyze the effects of variable GDP, inflation, interest rate, and exchange rate on share prices of the listed property sector in the Indonesia Stock Exchange. The object population in this study is a company incorporated in the listed property dan real estate index sector (JAKPROP) in the Indonesia Stock Exchange (BEI) from 2008 to 2017. This study uses Ordinary Least Square analysis to determine the effect of independent variables on the property and real estate index sector JAKPROP. Based on the t-test, GDP is significant, inflation is not significant, and the BI interest rate has a significant effect, while the variable exchange rate has a significant effect on property and real estate sector stock price index. Results simultaneously with the F test showed that all the independent variables significantly influence the stock price index property dan real estate sector. So, the result is the independent variable GDP, BI interest rate, and exchange rate have an influence effect on the stock price index of the listed property and real estate sector JAKPROP in the Indonesia Stock Exchange.